OCCURRENCE AND DISTRIBUTION OF MOLLUSCA FAMILY TROCHIDAE AT BADI ISLAND SW-SULAWESI INDONESIA - Litaay, M. (Marine Research in Indonesia, 2006)
The occurrence and distribution of family trochidae at Badi Island, Spermonde Archipelago off SW-Sulawesi has been studied. The line transect with combination of quadrant method was used during sampling. A transect covering 400 m' of sampling area was applied at 1, 3,5, and 7 m depth, respectively. Parameters such as shell length and size-class distribution were observed. Ecological parameters were also recorded during investigation. We found the presence of 11 species of trochidae at the study area. It was evident that some trochidae were common and while top shell Trochus niloticus seems to be rare. Vertical distribution among this group was uneven. The number of species decreases with increasing depth. Furthermore, high density of smaller trocha occurred at shallow water followed by a decline with changes in depth.